THE EFFORTS OF ACTS AND MORALS TEACHERS IN GUIDING RELIGIOUS MODERATION AT STATE TSANAWIYAH MADRASAH 2, JAMBI CITY - Rachmat Sholahuddin Febry; Rasidin Rasidin; M. Thontawi (Journal of Islamic and Interdisciplinary Research, 2025)
This study aims to determine the efforts of Akidah Akhlak teachers in fostering religious moderation at MTsN 2 Jambi City. This study uses a qualitative method with data collection techniques through observation, interviews, and documentation. Data were analyzed descriptively-qualitatively to describe strategies and challenges in fostering religious moderation. The research findings show that efforts to foster religious moderation are carried out inside and outside the classroom. In the classroom, teachers insert moderation values such as tolerance, justice, balance, deliberation, middle ground, and equality, all of which are related to students' daily lives. Outside the classroom, coaching focuses on strengthening national values and local culture through extracurricular activities and national moments. The obstacles faced include students' lack of understanding due to an unsupportive environment and the influence of social media that spreads extreme information. Strategic efforts involve all elements of the madrasah, including the principal, through synergy, role models, and integration of moderation values in activities and curriculum.